Efficacy and safety of different radiotherapy doses in neoadjuvant chemoradiotherapy in patients with locally advanced rectal cancer: A retrospective study - Xu, Yuyan; Zou, Haizhou; Shao, Zhenyong; Zhang, Xuebang; Ren, XiaoLin; He, Huijuan; Zhang, Dahai; Du, Dexi; Zou, Changlin (Frontiers in Oncology, 2023)
Abstract Background: This study aims to compare the efficacy and safety of neoadjuvant chemoradiotherapy (nCRT) with different radiotherapy doses (45Gy and 50.4Gy) in patients with locally advanced rectal cancer (LARC). Methods: Herein, 120 patients with LARC were retrospectively enrolled between January 2016 and June 2021. All patients underwent two courses of induction chemotherapy (XELOX), chemoradiotherapy, and total mesorectum excision (TME). A total of 72 patients received a radiotherapy dose of 50.4 Gy, while 48 patients received a dose of 45 Gy. Surgery was then performed within 5-12 weeks following nCRT. Results: There was no statistically significant difference between the baseline characteristics of the two groups. The rate of good pathological response in the 50.4Gy group was 59.72% (43/72), while in the 45Gy group achieved 64.58% (31/48) (P>0.05). The disease control rate (DCR) in the 50.4Gy group was 91.67% (66/72), compared to 89.58% (43/48) in the 45Gy group (P>0.05). The incidence of adverse reactions for radioactive proctitis, myelosuppression, and intestinal obstruction or perforation differed significantly between the two groups (P<0.05). The anal retention rate in the 50.4Gy group was significantly higher in contrast to the 45Gy group (P<0.05). Conclusions: Patients receiving a radiotherapy dose of 50.4Gy have a better anal retention rate but also a higher incidence of adverse events such as radioactive proctitis, myelosuppression, and intestinal obstruction or perforation, and a comparable prognosis to patients treated with a radiotherapy dose of 45Gy.